Sweet Corn - Marr, Charles W.; Tisserat, Ned (My University, 1995)
This publication is for commercial vegetable production, specifically sweet corn in Kansas.
MF1106_1995_01
Keywords: MF1106; Crops; Fruits and Vegetables; Equipment and Structures; MF